2016
DOI: 10.1186/s12889-016-3051-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of the signs and symptoms and risk factors of lung cancer in Australia: mixed methods study

Abstract: BackgroundLung cancer is the leading cause of cancer death in Australia. There is potential that health promotion about the risks and warning signs of lung cancer could be used to reduce delays in symptom presentation when symptoms are first detected. This study investigated knowledge, attitudes and beliefs which might impact help-seeking behaviour and could provide insight into possible public health interventions in New South Wales (NSW).MethodsA convergent mixed method study design was used wherein data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 29 publications
5
49
1
Order By: Relevance
“…Types of malignant cancer based on the result of this study were skin, liver, stomach and oral cavity cancer. This result has a contradiction with several studies that stated most of the type of cancer due to smoking habit is lungs cancer (Morris et al, 1997;Furrukh, 2013;Crane et al, 2016;Spits and Neefjes, 2016). However, previous studies stated that there are at least 17 types incident of cancer due to cigarette smoking behaviour (Baade, 2015; and >30 cigarettes per day and the risk of having cancer showed 93.8% and 95.5%, respectively.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Types of malignant cancer based on the result of this study were skin, liver, stomach and oral cavity cancer. This result has a contradiction with several studies that stated most of the type of cancer due to smoking habit is lungs cancer (Morris et al, 1997;Furrukh, 2013;Crane et al, 2016;Spits and Neefjes, 2016). However, previous studies stated that there are at least 17 types incident of cancer due to cigarette smoking behaviour (Baade, 2015; and >30 cigarettes per day and the risk of having cancer showed 93.8% and 95.5%, respectively.…”
Section: Discussionmentioning
confidence: 72%
“…According to Catsburg et al, (2015) smoking 20-29 and 30-39 cigarette per day as a heavy smokers and increased risk of breast cancer at (HR=1.14 and HR=1.10, respectively) and result study of Morris et al, (1997) stated that smoking >25 cigarette per day increased risk 18 times to be diagnosed with lung cancer. Most recent epidemiological studies also find the consistency positive association between smoking and any types of cancer (Gandini et al, 2008;Young et al, 2009;Hansen et al, 2013;Alexandrov, 2016;Crane et al, 2016;Sohn and Jung, 2016;Spits and Neefjes, 2016). In Alexandrov, 2016).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…People may delay help-seeking due to poor knowledge of lung cancer symptoms (12,13), or wait until the disease advances to a terminal stage (14,15). Lack of public awareness of lung cancer and recognition of what to do when symptoms develop contribute to this delay (16,17). Early recognition by patients about the signs and symptoms of lung cancer depends on their level of awareness (4).…”
Section: Introductionmentioning
confidence: 99%
“…Over 90% of patients with lung cancer are symptomatic at the time of diagnosis and experience two to three symptoms on average (27,28). Cough is the most common presenting symptom and has been noted to be a good prognostic indicator (14,17,27). It has also been shown that many patients will visit their general practitioner (GP) on more than one occasion before further investigation or onward referral (27).…”
Section: Introductionmentioning
confidence: 99%